Upaya Lembaga Zakat Yatim Mandiri Tulungagung dalam Meningkatkan Kualitas Anak Yatim dan Dhuafa Melalui Program Pendidikan Sanggar Genius - Lailatul Nurrohmah; Ahmad Supriyadi; Muhammad Alhada Fuadilah Habib (Universitas Islam Negeri Sunan Ampel Sunan Ampel, 2022)
The efforts made to improve the quality of orphans and poor people through the genius studio education program are ways or forms that are carried out in order to meet the needs in the form of quality free tutoring and the learning system focuses on mathematics and morals so that the quality of education for orphans and dhuafa increases. From this background, research was carried out to examine the formulation of problems, including: 1) How the efforts of the of the National Amil Zakat Institute for Yatim Mandiri Branch of Tulungagung to improve the quality of orphans and poor people through the genius studio education program, 2) What are the obstacles and how the solutions are carried out by the Yatim Mandiri National Amil Zakat Institute, Tulungagung Branch in improving the quality of orphans and poor people through the genius studio education program. This research is a field research using a qualitative approach, in which data is obtained through observation, interviews, and also documentation. This research was conducted at LAZNAS Yatim Mandiri Tulungagung Branch. The results of this study indicate that, firstly: efforts made in order to improve the quality of education for orphans and poor people in the genius studio, namely the presence of educators, providing motivation, encouraging them to be independent in working on questions, given handcraft training, given conceptual learning assistance, then conduct an evaluation. Second: the obstacles faced in improving the quality of education for orphans and poor people include lack of cooperation between the institution and the children's environment, the number of similar programs with LAZ or BAZ so that these programs can compete, funding constraints, lack of enthusiasm for learning, and lack of encouragement from families to take part in the tutoring process at the genius studio.